Question -
Answer -
Solution:
We are given with the polynomial here,
p(x) = x3-3x2+x+1
And zeroes are given as a тАУ b, a, a + b
Now, comparing the given polynomial withgeneral expression, we get;
тИ┤px3+qx2+rx+s = x3-3x2+x+1
p = 1, q = -3, r = 1 and s = 1
Sum of zeroes = a тАУ b + a + a + b
-q/p = 3a
Putting the values q and p.
-(-3)/1 = 3a
a=1
Thus, the zeroes are 1-b, 1, 1+b.
Now, product of zeroes = 1(1-b)(1+b)
-s/p = 1-b2
-1/1 = 1-b2
b2┬а= 1+1 = 2
b = тИЪ2
Hence,1-тИЪ2, 1 ,1+тИЪ2 are the zeroes of x3-3x2+x+1.